PENYEBAB PENGGUNAAN SINONIM - Isa, Arie Andrasyah (Jurnal Pujangga, 2010)
Synonym happens both in lexeme and paraphrase. Synonym can be divided into two kinds; close and absolute synonyms. Synonym might happened because of the differences among dialect, variety of language, euphemism, jargon, situation of language, nonstandard language, also social class. Synonym is created to soften several idioms which sound rude to particular societies.